A fatal lie [large type] - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels, 2021)
"A peaceful Welsh village is thrown into turmoil when a terrified boy discovers a body in the river. The man appears to have fallen from the canal aqueduct spanning the valley. But there is no identification on the body. The local police turn to Scotland Yard for help. Inspector Ian Rutledge is given few clues to go on--a faded military tattoo on the victim's arm and an unusual label in his shirt. But eventually they do lead to the victim's identity: Sam Milford, an Englishman. By all accounts, he was a good man and well respected. Then why is his death so mysterious?"--Page 4 of cover.